Zarządzanie wiedzą w instytucjach samorządowych - Morawski, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The author of article presents the basic foundations of conception of knowledge management. It was underlined the necessity of complex approach to creating of system of knowledge management at organization. The implementing the strategy of management serves this proper the knowledge, introduced on example of council institutions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 648-657